الاستثمار الاجتماعي المسؤول و دوره في تعزيز التنمية المستدامة-دراسة حالة مشروع Agid لولاية سيدي بلعباس (الجزائر) - ناصري, ايمان; سمرد, نوال (جامعة الوادي - University of Eloued, 2020)
The aim of this research is to identify responsible social investment as a modern investment, its importance and its lessons in promoting sustainable development, based on the descriptive and case study approaches, and to present the leading experience in responsible social investment in Sidi BelAbbas (Algeria). The Agid project, which strives to integrate environmental and social concerns into its programs and strategies and to promote sustainable development, on the one hand, is profitable for the national economy on the other. The study concluded in the last few days a series of results, including that responsible social investment became the main concern in implementing development programs and plans, and it became a concern for officials and decision makers, taking a clear lead in the decline of oil revenues and the decline of Algeria's hard currency incomes
Responsible Social Investment and its role in promoting Sustainable Development - A case study of the AGID project for the state of Sidi Bel Abbes (Algeria)
مقال
Keywords: المسؤولية الاجتماعية ; الاستثمار ; الاستثمار الاجتماعي المسؤول ; التنمية المستدامة